Characterisation and transferability of transcriptomic microsatellite markers for Nothofagus species - El Mujtar, Veronica Andrea; Lopez, Micaela; Amalfi, Sabrina; Pomponio, Maria Florencia; Marcucci Poltri, Susana Noemi; Torales, Susana Leonor (2017)
Discriminant molecular markers are required for research on population genetics, as well as evolutionary studies involving identification of hybrids and parental species, or detection of the genome regions under selection. We provide a set of 27 transcriptomic microsatellite markers (SSRs) for South American Nothofagus species, derived from 73 Nothofagus alpina (=N. nervosa) annotated unigenes. Rates of cross-amplification ranged from 22% to 37%. Genetic characterisation of 22 transcriptomic SSRs for N. alpina and N. obliqua reveals low genetic variability, due to the general occurrence of one major allele at each locus, and high specificity, with few alleles shared between species (14%). At inter-species level 95% of loci were discriminant, with a total G’’st over loci of 0.9, indicating that alleles were mostly fixed for all loci in both species. At intraspecies level the number of markers with significant differentiation was 2.5 times higher for N. obliqua than for N. alpina populations. Moreover, transcriptomic SSRs showed higher performance compared with published anonymous microsatellites isolated from genome sequences without annotation. This set of transcriptomic microsatellites will be useful to the scientific community working on conservation and evolutionary aspects of Nothofagus species.